The socio-cultural characteristics of posthistoricity. to have or be? - Alaverdyan, Nelli (Bulletin of Yerevan University E: Philosophy, Psychology, 2022)
The society, which has appeared in this new social situation, is going to face with the dilemma of destruction or survival. Abrupt changes bring with them not only the need of society’s reconstruction, introduction and operation of new social institutes, but also the need of adequate changes in the cultural and socio-psychological basis of society. At the current stage of civilizational developments, instability and uncertainty have become characteristic features of social life. The speed of innovation underlying technogenic civilization in the 21st century leads to the renewal of the artificial environment, which creates controversial relations with the equally important aspects of human existence and society’s existence: stability. The ongoing radical transformations are also changing the structure of the artificial environment, one of the necessary foundations of human activity. Information technology that has penetrated almost in all spheres of public and private life, create some type of virtual world instead of the natural-physical. Along with the spread of the new so-called mass and information culture, the rift between generations is going deeper. A person, who finds himself in uncertainty loses control over the economic conditions of his own life, which forces him to reconside his entire value system. The modern material world is gradually losing its certainty and duration of existence. Breaking away from national roots, radical transformations of ethnic identity and national characteristics become a danger for society. The clash between civilizations, the contradictions between liberal civilization and fundamental national-cultural values, put with split consciousness person, who’s also suffering from complicated and controversial tendencies, in front of the most important problem: "to have or to be?"